A cladistic analysis and reclassification of the tribe Bembicini (Hymenoptera: Crabronidae: Bembicinae) - Nemkov, Pavel G.; Ohl, Michael (Zootaxa, 2011)
A cladistic analysis of the digger wasp tribe Bembicini based on morphological characters is presented. The underlying data matrix comprises 64 terminal taxa (coded on genus-level) and 54 morphological characters. The resulting strict consensus tree was used as the basis for a revised subtribal classification of the Bembicini. Based on a previously published classification, we herewith propose a number of changes. The subtribe Spheciina Nemkov and Ohl, subtrib. nov. (comprising Ammatomus A. Costa 1859, Kohlia Handlirsch 1895, Sphecius Dahlbom 1843, and Tanyoprymnus Cameron 1905) is removed from Handlirschiina Nemkov and Lelej 1996. The subtribe Stictiellina Bohart and Horning 1971, stat. resurr. (composed of Chilostictia Gillaspy 1983, Glenostictia Gillaspy in Gillaspy, Evans, and Lin 1962, Microstictia Gillaspy 1963, Steniolia Say 1837, Stictiella J. Parker 1917, and Xerostictia Gillaspy 1963) is separated from Bembicina Latreille 1802. The subtribe Argogorytina Nemkov and Lelej 1996 (Argogorytes Ashmead 1899, Neogorytes Bohart in Bohart and Menke 1976, Paraphilanthus Vardy 1995) is synonymized with Exeirina Dalla Torre 1897, syn. nov. Finally, the subtribe Trichogorytina Nemkov and Pulawski 2009 (genus Trichogorytes Rohwer 1912 only) is synonymized with Gorytina Lepeletier de Saint Fargeau 1845, syn. nov. An updated identification key to the subtribes of the Bembicini is provided.